Effects of heart rate reduction with ivabradine on vascular stiffness and endothelial function in chronic stable coronary artery disease - Hohneck, Anna; Fries, Peter; Ströder, Jonas; Schneider, Günther; Wagenpfeil, Stefan; Schirmer, Stephan; Böhm, Michael; Laufs, Ulrich; Custodis, Florian (Journal of hypertension, 2019)
Epidemiological and clinical studies have shown a relevant association between heart rate and cardiovascular mortality. Experimental studies identified vascular effects of heart rate reduction with the If channel inhibitor ivabradine. Therefore, the effects of heart rate reduction on en